Biodiversidade do cerrado : percepção e estratégias para o ensino de ciências - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The CTSA Education (Science, Technology, Society and Environment) sets a trend that can help change the distorted vision one has of science and can offer real scientific literacy opportunities for citizens. educational activities in non-formal spaces can help to stimulate attitudes in environmental conservation. When the citizen is recognized as an integral part of the environment, he feels - is responsible for the conservation of resources, showing respect regarding the use of this environment. Interpretative trails are non-formal spaces used to share experiences that take visitors (students, teachers, students or tourists) to understand, to raise awareness and to cooperate in the conservation of natural resources. The interaction of the subject with the track shown essential in the learning process, as it is triggered the individual's perception of the process. Thus, this study aims to evaluate the environmental perception of elementary school students on the biodiversity of the Cerrado, and propose and test a didactic sequence in non-formal environment for the Cerrado biodiversity education. It is a qualitative and quantitative approach to research. The research is divided into three phases, the first phase of an evaluation stage of awareness about the biodiversity of the Cerrado, with the use of semi-structured questionnaire and preparation of drawings by 243 elementary students of municipal schools of Anápolis / GO. The second step is the development of the didactic sequence for non-formal settings. The third phase is the validation of the sequence in which students participate in activities in an interpretive trail and lecture on the Cerrado. At the end of the third stage, the students were again evaluated by means of semi-structured questionnaire and drawings of the students. Results obtained by students of the drawings of the evaluation can be seen that the environmental perception students have about the biodiversity of the Cerrado, the prevailing idea of a natural environment. However, students understand that human activities are interfering with the environment in a negative way, bringing irreparable consequences over the years. Through the evaluation of the designs of students, you can see that the interpretive trail strategy is more effective than the lecture so that students understand the Cerrado biodiversity elements. Thus, the interpretative trails are tools that can be effective to promote the popularization of knowledge of the Cerrado biome and its biodiversity since students can experience real experiences with previously only present content in textbooks.
Cerrado biodiversity : perception and strategies for teaching science
Keywords: CTSA; Sequência Didática; Espaços não-formais; CTSA; Didactic sequence; Non-formal spaces; CIENCIAS BIOLOGICAS; ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO